Interaction of the reflective ethnobiology (REBI) model and creative thinking argumentation in biodiversity material - Efriana Jon; A. Asrial; Muhammad Haris Effendi Hasibuan; Bambang Hariyadi (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
The ethnoscience-based reflective learning model has been implemented in the classroom while the learning process has its own strengths and weaknesses. The purpose of this study was to determine the interaction between learning models and arguments for creative thinking. A mixed methods research design was applied to collect both qualitative and quantitative data. Quantitative data were collected using argumentation observations and essay tests which were analyzed with SPSS. Qualitative data sourced from one lecturer and 40 students of National Islamic Institute of Kerinci, Jambi Province were collected using interviews and observations. The results shows that there is an interaction between learning models and arguments for creative thinking. This can be seen from the whole learning process students have achieved indicators of creative thinking involving argumentation skills. We discussed this and formulated recommendations that can be implemented in the future.